Exploring the Challenges Teachers Face in Using the Integrated Approach in Teaching Language in Junior High Schools in HOHOE Municipality - Adansi, Joana Emefa; Adukpo, John (Cascades, Journal of the Department of French & International Studies, 2025)
This study aimed to investigate the challenges encountered by teachers in implementing the integrated approach to language instruction in junior high schools within Hohoe Municipality. The primary element influencing this study was the inadequate academic performance of students in the English language. The integrated method is essential in English language instruction and facilitates the enhancement of learners’ linguistic abilities. The research was founded on the principles of Basil Bernstein’s theory and reinforced by Theodore Frick’s Integrated Education Theory. The research employed a qualitative methodology, utilising interviews with 10 circuit supervisors, 10 department heads, and 10 English teachers in Junior High Schools. It sought to furnish a thorough comprehension of a research topic by initially gathering qualitative data for elucidation. This strategy enabled researchers to attain a more profound comprehension of the research problem via qualitative methodologies. In this study, the researcher conducted interviews with teachers, department heads, and circuit supervisors. Interview questions for Heads of Departments (language) focused on the solutions implemented to address the obstacles faced by teachers in instructing the English language. The study revealed several challenges, including inadequate teaching materials, a classroom environment that occasionally hindered teachers from engaging students in discussions or oral interactions, and the impact of vernacular languages that frequently disrupted English instruction. The study indicated that the curriculum content was often comprehensive and necessitated significant time allocation, which was insufficient in the current context, presenting a challenge. The study advised that to guarantee the efficient implementation of an integrated approach to English instruction in classrooms, educational stakeholders must establish policies and oversee teachers. Government authorities must to engage with educators to comprehend the difficulties encountered in executing an integrated approach within educational institutions.